Topical Problems of New Georgian Literature - Baladze, Malkhaz ("Intercultural Dialogues" Transactions, 2021)
The history of new Georgian literature begins with Romanticism. Its origin was facilitated by the historical process that developed in Georgia at the beginning of the 19th century, in particular, the loss of the country's independence. The Georgian man left the field of action, he became dependent on others. Sadness and despair, in turn, gave rise to a certain spiritual loneliness in Romantic writers. Loneliness even added more judgmental character to their creativity. Questions arose about human life, destiny, its essence and purpose, which in itself gave the creations of the Romantics a philosophical character. Thus, Georgian literature has already responded to the world historical-philosophical proces, Where the problem of the place of art, starting from the era of Romanticism, permeated the entire humanitarian self-knowledge of European culture. The subject of research is also the question, what philosophy means in literature, What is the difference between philosophy and the philosophy of literature and what do they have in common, When philosophy thinks in categories, literature in artistic forms and these two forms of conveying truth are important to man. Georgian classical romanticism begins with Alexander Chavchavadze and he laid the foundation for the artistic-philosophical understanding of the events and carried out the philosophical contemplation of the essence and existence, purpose and origin of human life in excellent artistic forms;The elements of philosophical reasoning in the work of Gregory Orbeli are faint, but still appear in the last period of creation.The peak of Georgian romanticism, Nikoloz Baratashvili, takes the philosophical character of Georgian literature of that time to the highest level. The difference is that the internal philosophical discourse with Nikoloz Baratashvili goes to the highest level and not only philosophically prepares us for certain events, but, in many cases, responds to them.In the second half of the 19th century, realism further deepened the process of depicting these important issues in a highly artistic form, which is the subject of a separate study.